Mineral nitrogen fertilization effects on lettuce crop yield and nitrogen leaching - Sylvestre, Thiago de Barros; Braos, Lucas Boscov [UNESP]; Batistella Filho, Felipe; Cruz, Mara Cristina Pessôa da [UNESP]; Ferreira, Manoel Evaristo [UNESP] (Elsevier, 2019)
The low efficiency of N fertilization in soils used to grow vegetables and the consequent need to add high levels of the nutrient are the major cause of nitrate contamination of groundwater and freshwater, which calls for practices to increase N fertilization efficiency in these crops. Two experiments were carried out in Jaboticabal, Brazil, to evaluate the effects of topdressing N fertilization on crisphead lettuce (Lactuca sativa)yield, nitrate accumulation in plant shoots, and soil nitrogen leaching in two growing seasons, summer and winter. Both experiments were designed as randomized blocks with seven treatments and five replications (35 plots). The treatments were seven different rates of topdressing N. The rates of N application were 0, 30, 60, 90, 120, 150, and 180 kg N ha -1 in the form of urea, applied 8 (20%), 16 (40%), and 24 (40%)days after transplanting. Lettuce was harvested 34 and 42 d after transplanting in the summer and winter, respectively. Plant nitrate concentrations were determined in dry matter. After the harvest, soil samples were collected at the 0-20, 20-40, and 40-60 cm layers to quantify nitrogen in the forms of ammonium and nitrate. The data were submitted to analysis of variance and nonlinear regression analysis. Better use of topdressing nitrogen fertilization for lettuce growth was observed at rates lower than 60 kg N ha -1. Rates of N up to 180 kg N ha -1 did not elevate lettuce nitrate concentrations over the levels allowed for consumption but increased the amount of nitrogen lost through leaching. Decreasing N rates resulted in a similar yield and lower nitrogen leaching, improving both the environmental and economic aspects.
Keywords: Fertilization efficiency; Lactuca sativa; Nitrate; Topdressing